Role of Kasturba Gandhi Balika Vidyalaya in the Educational Development of Scheduled Tribe Girls in Jharkhand - Mandal, Pushpa (JOURNAL OF INDIAN EDUCATION, 2009)
Elementary education for all the children of age group 6-14 years in the India is an essentiality. It is considered as fundamental to all round development of the individual, both at material and spiritual levels. Elementary education is known to lead to better family health and slower population growth. It creates in the individual, the capacity to take advantage of technological changes, leading to enhancement in productivity and economic benefit.